12-3(2w+1)=7w-3(7w+w)

Simple and best practice solution for 12-3(2w+1)=7w-3(7w+w) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12-3(2w+1)=7w-3(7w+w) equation:


Simplifying
12 + -3(2w + 1) = 7w + -3(7w + w)

Reorder the terms:
12 + -3(1 + 2w) = 7w + -3(7w + w)
12 + (1 * -3 + 2w * -3) = 7w + -3(7w + w)
12 + (-3 + -6w) = 7w + -3(7w + w)

Combine like terms: 12 + -3 = 9
9 + -6w = 7w + -3(7w + w)

Combine like terms: 7w + w = 8w
9 + -6w = 7w + -3(8w)

Remove parenthesis around (8w)
9 + -6w = 7w + -3 * 8w

Multiply -3 * 8
9 + -6w = 7w + -24w

Combine like terms: 7w + -24w = -17w
9 + -6w = -17w

Solving
9 + -6w = -17w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '17w' to each side of the equation.
9 + -6w + 17w = -17w + 17w

Combine like terms: -6w + 17w = 11w
9 + 11w = -17w + 17w

Combine like terms: -17w + 17w = 0
9 + 11w = 0

Add '-9' to each side of the equation.
9 + -9 + 11w = 0 + -9

Combine like terms: 9 + -9 = 0
0 + 11w = 0 + -9
11w = 0 + -9

Combine like terms: 0 + -9 = -9
11w = -9

Divide each side by '11'.
w = -0.8181818182

Simplifying
w = -0.8181818182

See similar equations:

| 2(x-1)=4x-4 | | 2x+2x-9=11 | | 4=5C-(-14) | | 5t-1=60-5 | | 1/2(-3)+5 | | -7/6x+5/4x=2 | | b+17=33 | | 4x-y=3y-7 | | -47+n=13 | | -6/-20 | | x^3-5x^2-23x-8=0 | | 5th-1=60-5 | | 1/j+1/n=1/u | | n+4/-16=-1 | | n-20=-1 | | 9c^2+6c-35=0 | | 5(3-x)+3x=6(2x) | | -7/4(5/4a+1)+7/6=-1561/1200+7/5a | | 5(2x+6)=-41-5-2x | | 5(3-x)+3x=12x | | 5/2=98-n | | 2=(4/3)-(5/z) | | 15-x+5=80 | | (3x^4/3)-7=41 | | (28x-4x^2)/(32x+12) | | 22-y=2 | | s^2-8s+2=0 | | 3x^4/3-7=41 | | a=-70+(-3b) | | 5/4/13/4=7/x | | 5-3(2-x)=0 | | 15x^2+20x-12=0 |

Equations solver categories